REPRESENTASI HADIS DALAM SINETRON INDONESIA - Rohimi, Primi (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2018)
The aim of this study is to show how the hadith is represented in sinetron (soap operas). What is the meaning behind the representation. It is motivated by the existence of pros and cons of the use of hadith in sinetron. Some soap operas are claimed to be preaching media to display hadiths in various ways. This study uses a semiotic method that can show how the hadith is displayed in sinetron. This method can also capture the meaning behind the appearance of the hadith. The result is as a consequence of the product of media with its two sides. Sinetron display the hadith in a sacred way, namely with the original Arabic text dialogues and their meanings. The speaker is also religious in character. As in the Dunia Terbalik sinetron, the hadith is often read by Kusoy. But, the hadiths appear in soap operas as decoration so they tend to be profane.